Creating Equipment for Low-Temperature Study of Current-Voltage Characteristics and Galvanomagnetic Properties of Semiconductor Materials and Structures in the Field of an External Magnet - ZHARKOV, I.; SAFRONOV, V.; KHODUNOV, V.; KONOVAL, V.; PALAMARHUK , I.; SELIVANOV, O.; SOLONETSKY, А.; ALEYNIKOV, A.; VIRKO, S. (Science and Innovation, 2022)
Introduction. The study of volt-ampere characteristics (VAC) and galvanomagnetic properties of semiconductor materials and structures based on them under the action of microwave radiation and magnetic fields in a wide range of temperatures is an urgent task for the development of the element base of spintronics and supersensitive sensors. Problem Statement. Currently, there has been no precision complex of thermoregulated cryogenic equipment for low-temperature studies of VAC and galvanomagnetic properties of semiconductor materials and structures based on them in the field of the external magnet, which fully meets the needs of studying the parameters of superconducting materials. Purpose. The purpose of this research is to design and to manufacture a single computerized complex of thermoregulated cryogenic equipment. Materials and methods. Based on the existing domestic experience of creating cryosystems for magnetophysical studies and accessories to them, the development and manufacture of a set of thermally regulated cryo-genic equipment for studying the volt-ampere characteristics and galvanomagnetic properties of semiconductor materials and structures based on cryostat with a specialized manipulator. Results. As a result of the research, we have created a complex of precision cryogenic equipment as a part of a cryosystem thermoregulated within 1,5–300 К, based on a helium continuous flow cryostat with a narrow shank. The system consists of an external magnet built into the interpolar space, a specialized manipulator having a built-in gauge for measuring the liquid helium level in the cryostat shaft, a temperature controller, modules for measuring the volt-ampere characteristics and galvanomagnetic properties of semiconductor materials, and software. Conclusions. The designed equipment has as good characteristics as the best western analogs and exceeds them in terms of cryoagent consumption and costs of its maintenance and service.